2018 IEEE 16th International Conference on Industrial Informatics (INDIN) 2018
DOI: 10.1109/indin.2018.8471951
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Integration of Software Agents and Industrial Automation Systems with ISO/IEC 25010

Abstract: Agent-technologies have been used for higher-level decision making in addition to carrying out lower-level automation and control functions in industrial systems.Recent research has identified a number of architectural patterns for the use of agents in industrial automation systems but these practices vary in several ways, including how closely agents are coupled with physical systems and their control functions. Such practices may play a pivotal role in the Cyber-Physical System integration and interaction. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Surely there are no "onesize-fits-all" solutions, but nevertheless, when considering the specific characteristics of most industrial requirements some issues may emerge. For instance, in a small survey [13], carried out among the IEEE P2660.1 working group [18] experts, it emerged that testability is seen as much more important than others (e.g., the user interface aesthetics). However, as seen in Table I, the three proposed measures for assessing testability range from neutral, to good or very good.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surely there are no "onesize-fits-all" solutions, but nevertheless, when considering the specific characteristics of most industrial requirements some issues may emerge. For instance, in a small survey [13], carried out among the IEEE P2660.1 working group [18] experts, it emerged that testability is seen as much more important than others (e.g., the user interface aesthetics). However, as seen in Table I, the three proposed measures for assessing testability range from neutral, to good or very good.…”
Section: Discussionmentioning
confidence: 99%
“…In software systems research, several quality attributes and metrics are studied [10], [11]. Standards, such as ISO/IEC 25010 [12], define several high-level characteristics which are relevant to this context [13]. However, to be able to get a quantifiable assessment, there is a need to check the concrete measures and their calculation as proposed by ISO/IEC 25023 [14] which also belongs to the same standards family.…”
Section: Introductionmentioning
confidence: 99%
“…Each characteristic is then further separated into multiple sub-characteristics. Subsequently, a survey was conducted with a team of experts in the domain to identify qualities that are most relevant to the field [6]. The survey found that testability, availability, time behavior, interoperability, availability, fault-tolerance and reusability emerged as the most important characteristics for the practices.…”
Section: Introductionmentioning
confidence: 99%
“…The IEEE P2660.1 standardization project, "Recommended Practices on Industrial Agents: Integration of Software Agents and Low Level Automation Functions", has been working on a methodology to rank and select best-fit Industrial Agent practices for the interfacing between software agents and automation control devices. Previous work was devoted to identifying the patterns derived from a survey of existing implementations of industrial agents [5], and to assess their characteristics, using the ISO/IEC 25010 standards family as a starting point [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation